ANALISIS KESIAPAN SISTEM ADMINISTRASI PERPAJAKAN DIGITAL DALAM MENGAKOMODASI PERUBAHAN TARIF PPN TAHUN 2025 - Putri, Nadia Shinta Okta; Widodo, Ulfa Puspa Wanti (JURNAL AKUNTANSI BARELANG, 2025)
This study aims to analyze the readiness of the digital tax administration system in facing the change in VAT rates to 12% in 2025, using the Technology Acceptance Model (TAM) approach. This study uses a descriptive qualitative method through interviews with three informants and literature studies. The focus of the study is directed at three main aspects: perceived usefulness, perceived ease of use, and system compliance with regulations. The results of the study indicate that the digital tax system, such as the Core Tax Administration System (CTAS), is considered useful in accelerating reporting and increasing efficiency. However, ease of use has not been felt evenly because there are still technical obstacles. In addition, although the new rates have been automatically accommodated, the initial implementation of the system was still marked by technical problems and lack of socialization. Further research is recommended to use a quantitative approach with a wider scope of respondents and additional variables such as trust in the system and infrastructure readiness.